2022
DOI: 10.1002/jbm4.10637
|View full text |Cite
|
Sign up to set email alerts
|

The Real‐World Effect of 12 Months of Romosozumab Treatment on Patients With Osteoporosis With a High Risk of Fracture and Factors Predicting the Rate of Bone Mass Increase: A Multicenter Retrospective Study

Abstract: Excluding clinical trials, there is limited evidence on the effect of 12 months of romosozumab treatment on bone mineral density (BMD) increase in real-world clinical practice because its use has only been approved recently. Thus, this study aimed to investigate the real-world effect of 12 months of romosozumab treatment on BMD increase and identify factors that predict the rate of BMD increase after 12 months of romosozumab treatment. We retrospectively investigated 106 patients who completed a 12-month romos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Of this patient subgroup, only half received fewer than six doses of romosozumab [4]. Realworld data from two Japanese cohort studies reported 3% and 5.7% of patients who suffered new fractures during treatment with romosozumab, of which 1.3% and 1.9% a vertebral fracture [9,10]. A recent retrospective study regarding 92 romosozumab non-responder patients found an absent early rise in P1NP to be a predictor of nonresponse at month 12 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Of this patient subgroup, only half received fewer than six doses of romosozumab [4]. Realworld data from two Japanese cohort studies reported 3% and 5.7% of patients who suffered new fractures during treatment with romosozumab, of which 1.3% and 1.9% a vertebral fracture [9,10]. A recent retrospective study regarding 92 romosozumab non-responder patients found an absent early rise in P1NP to be a predictor of nonresponse at month 12 [11].…”
Section: Discussionmentioning
confidence: 99%
“…Romosozumab has the dual effect of increasing bone formation and suppressing bone resorption, leading to significant increases in BMD [ 34 ]. In Japan, Inose et al (2022) recently reported that 106 osteoporosis patients at a high risk of fracture and treated with romosozumab for 12 months achieved BMD increases of 14.6% at the lumbar spine, 5.1% at the femoral neck, and 3.1% at the total femur [ 35 ]. Romosozumab was less effective for patients with prior treatment consisting of osteoporosis medication such as bisphosphonate, denosumab, and teriparatide [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Romosozumab increases bone density by continuously promoting bone formation and inhibiting bone resorption early after administration ( Cosman et al, 2016 ). A favorable increase in bone density with romosozumab use has been reported ( Cosman et al, 2016 ; Ebina et al, 2021 ; Inose et al, 2022 ; McClung et al, 2014 ). However, despite vitamin D and calcium supplementations during clinical trials, hypocalcemia is considered an adverse effect of romosozumab administration ( Cosman et al, 2016 ; McClung et al, 2014 ).…”
Section: Introductionmentioning
confidence: 94%